Study on Cashewnut in India - Planning Commission (Planning Commission, 1964)
The Planning Commission’s study on the cashew nut industry in India highlights its economic significance, employment potential, and export contribution. Predominantly cultivated in southern states, cashew trees thrive in poor, sandy, and hilly terrains. While domestic production reached 117,850 tonnes by 1961, processing capacity outstripped supply, creating reliance on imports. The study emphasizes the need for high-yield varieties, improved cultivation practices, and effective pest management. Strategic recommendations include plantation surveys, promotion of coastal cultivation, modernization of loans, demonstration plots, and cooperative structures for fair market access. Addressing underutilization of by-products and enhancing domestic production are key to meeting global demand. With focused planning and research, India can strengthen its position in the international cashew market and boost economic returns.
Committee on Natural Resources Planning Commission New Delhi
Committee on Natural Resources Planning Commission New Delhi
Keywords: Cashew Nut Industry; India; Cashew Cultivation; Export Earnings; Southern States; Production Statistics; High-Yield Varieties; Research and Development; Industrial Processing; Agricultural Recommendations